2008
DOI: 10.4269/ajtmh.2008.79.185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Exposure, Clinical Malaria, and Age in an Area of Changing Transmission Intensity

Abstract: The relationship between malaria transmission intensity and clinical disease is important for predicting the outcome of control measures that reduce transmission. Comparisons of hospital data between areas of differing transmission intensity suggest that the mean age of hospitalized clinical malaria is higher under relatively lower transmission, but the total number of episodes is similar until transmission drops below a threshold, where the risks of hospitalized malaria decline. These observations have rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 34 publications
8
82
1
Order By: Relevance
“…Several studies have shown a shift in the peak of acute malaria incidence toward older ages as malaria exposure wanes [14,63], which may precede changes in the number of episodes and disease spectrum in an area with declining transmission intensities [64]. These observations illustrate that sustained reduction in exposure to malaria infection leads to changes in mean age and presentation of disease [65].…”
Section: Disease Patterns During Changes Of Malaria Transmissionmentioning
confidence: 92%
“…Several studies have shown a shift in the peak of acute malaria incidence toward older ages as malaria exposure wanes [14,63], which may precede changes in the number of episodes and disease spectrum in an area with declining transmission intensities [64]. These observations illustrate that sustained reduction in exposure to malaria infection leads to changes in mean age and presentation of disease [65].…”
Section: Disease Patterns During Changes Of Malaria Transmissionmentioning
confidence: 92%
“…Usually, high levels of antibodies correlate with reduced parasitaemias,54 whereas antidisease effector processes are more associated with reduced levels of proinflammatory mediators, and are strongly associated with increased prior exposures 52, 55, 56, 57, 58, 59. As immunity against clinical episodes of malaria is positively associated with increased prior exposure (or age) in endemic areas,60, 61 antidisease mechanisms (targeted at ameliorating inflammation induced pathology) might be an important mechanism mediating protection against clinical symptoms. For instance, asymptomatic carriers harbour parasites without showing clinical symptoms are mainly found at high levels of exposure34 and generally have lower levels of proinflammatory cytokines, including tumour necrosis factor (TNF)‐ α and interferon (IFN)‐ γ , than symptomatic individuals 36, 62, 63…”
Section: Antidisease Immunity and Antiparasitic Immunity To Malaria: mentioning
confidence: 99%
“…The threshold parasitaemia associated with fever (pyrogenic threshold) differs depending on the prevailing transmission intensity, 94 such that in children from areas of low‐to‐moderate transmission intensities, symptomatic malaria is associated with comparatively lower parasitaemia58, 61, 95, 96 and fewer children harbour parasites in a healthy state (asymptomatic carriers) 34. In the high‐transmission areas, however, this is often not the case, as higher parasite prevalence is observed in a healthy state,95 and most importantly higher parasitaemias are observed during clinical bouts of uncomplicated malaria 58, 97.…”
Section: The Role Of Inflammation In Malarial Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations